The Model of Pedestrian Arrangement in the Commercial Area Corridor of Jalan Pattimura Medan - Wahyu Abdillah; Hajar Suwantoro; Devin Defriza Harisdani; Dwi Lindarto Hadinugroho; Novrial; Firman Eddy (Jurnal Koridor, 2025)
The development of Medan City is challenged by unplanned growth that triggers the phenomenon of urban sprawl, especially in the commercial area corridor of Jalan Pattimura. The change of residential functions into commercial areas triggers various problems such as congestion, decreased quality of the visual environment, crowding, and degradation of the vitality of the area. This study aims to formulate a humanist pedestrian arrangement model in the corridor with a smart growth approach and community participation as a local force (genius loci). This research prioritizes the concept of linkage, both visually, structurally, and collectively, in redesigning pedestrian space. By promoting local wisdom as the basis for revitalization, the results of this study are expected to guide public policy based on community development in the management of sustainable commercial areas in Medan City. Keyword: pedestrian arrangement, strip development, urban sprawl, Pattimura Medan